HARMS ASPECTS OF FAST FOOD FOR HUMAN LIFE - Odilova , Sadoqat Foziljonovna; Ochilova , Kumushoy Jaloliddinovna (Innovative Development in Educational Activities, 2023)
This article discusses the harmful effects of fast food on human life. At the same time, it was also discussed about the diseases caused through fast food in the human body.